Envisioning innovation: Does visionary leadership engender team innovative performance through goal alignment?. (11th December 2019) - Mascareño, Jesús; Rietzschel, Eric; Wisse, Barbara
Abstract : Visionary leaders paint an image of the future with the intention to persuade others to contribute to the realization of that specific future. In the current study, we test the hypothesis that visionary leadership stimulates team creativity and innovation because visionary leadership promotes goal alignment amongst team members which, in turn, facilitates team creativity and innovation. In an experimental study ( N = 50 groups), we found that goal alignment indeed mediated the relationship between visionary leadership and team creativity, but not between visionary leadership and team innovation. In a field study ( N = 308 respondents) we found visionary leadership to be related to both team creativity and innovation through goal alignment. Moreover, the field study also showed that communication quality strengthened the relationship between goal alignment and team innovation. We discuss the theoretical and practical implications of visionary leadership in teams where creativity and innovation are desirable team performance outcomes.